THE EFFECT OF COMPENSATION AND WORK DISCIPLINE ON EMPLOYEE PERFORMANCE THROUGH WORK MOTIVATION (CASE STUDY: SECRETARIAT OF DPRD DKI JAKARTA PROVINCE) - Bosman Butarbutar; Lenny Christina Nawangsari (Dinasti International Journal of Education Management And Social Science, 2022)
This study objective to determine and analyze more related to the effect of work discipline and compensation on employee-performance through work-motivation as an intervening variable (case study: the secretariat of the parliament of the province of DKI Jakarta). The research method used is a quantitative research method with causal. The research population is the Employees of the Secretariat of the parliament of the province of DKI Jakarta, the status of civil servant with a total sample of 100 respondents. Methods of data analysis using SEM-PLS. And the results indicated that compensation does not significantly affect work motivation. Work discipline has a significant effect on work motivation. Compensation does not have a significant leverage on employee performance. Work discipline has a significant effect on employee performance. Work motivation has a significant impact on employee performance. Work motivation has no impact in mediating compensation on employee performance. However, work motivation is influential in mediating work discipline on employee performance.